Characterization of SiC thin films deposited by HiPIMS - Leal,Gabriela (2014)
In this work thin films of silicon carbide (SiC) were deposited on silicon wafers by High Power Impulse Magnetron Sputtering (HiPIMS) technique varying the average power of the discharge on a stoichiometric SiC target. X-ray diffraction, Raman spectroscopy, scanning electron microscopy and profilometry were used to analyze the films. It was observed that high values of the average electric power favors the formation of C-C bonds, while low values of the power promote the formation of Si-C bonds. At high power, we have also observed higher deposition rates, but the samples present surface imperfections, causing increase in the roughness and decrease in the film uniformity.